Synthesis and evaluation of cytotoxic and Na+/K+-ATP-ase inhibitory activity of selected 5α-oleandrigenin derivatives - Michalak, Karol; Rárová, Lucie; Kubala, Martin; Čechová, Petra; Strnad, Miroslav; Wicha, Jerzy (European journal of medicinal chemistry, 2019)
Oleandrin, the major biologically active constituent of shrub Nerium oleander preparations of which have been used in traditional Mediterranean and Asian medicine, attracts a great deal of attention due to its pronounced anticancer activity. The synthesis of oleandrigenin model, 16β-hydroxy-3β-methoxy-5α-card-20(22)-enolide 16-acetate, from androstenolone acetate through 17β-(3-furyl)-intermediates has been developed. Several related 17β-(butenolidyl)- and 17β-(furyl)-androstane derivatives were synthesized and tested for in vitro cytotoxic and Na+/K+-ATP-ase inhibitory activities. Comparison of Na+/K+-ATP-ase inhibitory and cytotoxic activity underlines complex nature of the relationship.
Keywords: inhibitory enzymů; Furan transformation; Nerium; buněčné linie; fytogenní protinádorové látky; Enzyme Inhibitors; vztahy mezi strukturou a aktivitou; Cytotoxicity; Dose-Response Relationship, Drug; Antineoplastic Agents, Phytogenic; screeningové testy protinádorových léčiv; Cardenolides; lidé; vztah mezi dávkou a účinkem léčiva; kardenolidy; Structure-Activity Relationship; molekulární konformace; Drug Screening Assays, Antitumor; Cell Proliferation; Cell Line; Humans; Sodium-Potassium-Exchanging ATPase; sodíko-draslíková ATPasa; Molecular Conformation; ATP-ase inhibition; proliferace buněk; Partial synthesis